EVALUATION OF CONTINUOUS GLUCOSE MONITORING (isCGM) ON TYPE 2 DIABETES PATIENTS TREATED WITH BASAL – BOLUS INSULIN THERAPY - Nguyen, Thuy Duong; Nguyen, Quang Bay; Nguyen, Khoa Dieu Van (Tạp chí Sinh lý học Việt Nam, 2023)
*]:pointer-events-auto R6Vx5W_threadScrollVars scroll-mb-[calc(var(--scroll-root-safe-area-inset-bottom,0px)+var(--thread-response-height))] scroll-mt-[calc(var(--header-height)+min(200px,max(70px,20svh)))]" dir="auto" data-turn-id="request-WEB:bec541d7-8a03-4ccc-a81b-8d17355ef112-34" data-turn-id-container="request-WEB:bec541d7-8a03-4ccc-a81b-8d17355ef112-34" data-testid="conversation-turn-70" data-turn="assistant"><div class="text-base my-auto mx-auto pb-10 [--thread-content-margin:var(--thread-content-margin-xs,calc(var(--spacing)*4))] @w-sm/main:[--thread-content-margin:var(--thread-content-margin-sm,calc(var(--spacing)*6))] @w-lg/main:[--thread-content-margin:var(--thread-content-margin-lg,calc(var(--spacing)*16))] px-(--thread-content-margin)"><div class="[--thread-content-max-width:40rem] @w-lg/main:[--thread-content-max-width:48rem] mx-auto max-w-(--thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn" data-conversation-screenshot-content=""> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal outline-none keyboard-focused:focus-ring [.text-message+&]:mt-1" dir="auto" tabindex="0" data-message-author-role="assistant" data-message-id="0d3567df-eb2d-48c1-ab59-19e9e8986274" data-message-model-slug="gpt-5-5" data-turn-start-message="true"> Objective: Evaluate effectiveness of continuous glucose monitoring (isCGM) on type 2 diabetes patients treated with basal–bolus insulin therapy. Method: Descriptive and interventional study on 29 type 2 diabetes patients treated with basal–bolus insulin therapy at Department of Endocrinology and Diabetes, Bach Mai Hospital from 1/2023 to 7/2023. Results: Average age is 61.4 ± 17.4. The majority oral antidiabetic drug is Metformin combined with Anti DDP4 (37%), bolus insulin is Regular (73%), basal insulin is Glargine U100 (97%). Average HbA1c is 10.8 ± 2.8%, average serum glucose on arrival is 17.2 ± 11.6 mmol/L. Time in range on 14th day 66.2 ± 16.9% higher than the 1st day 55.1 ± 29.0% (p = 0.03). CGM can detect more hypoglycemia events than point-of-care capillary blood glucose (34.2% versus 17.2%). Adverse reaction rate is 3.4% only. Conclusion: Continuous glucose monitoring is not only useful in controlling blood glucose level but also in detecting more hypoglycemia events than point-of-care capillary blood glucose.